Myanmar health professionals' educational needs: a pilot study - Mosca, Gloria; Cappi, Valentina; D'Apice, Clelia; Rossi, Sandra; Artioli, Giovanna; Sarli, Leopoldo (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: The main factor hindering the development of the Myanmar health system lies in the scarcity of financial and human resources attributed to the health system. This paper presents the preliminary results of a pilot study on the educational needs of Myanmar health professionals, addressing the empowerment of human resources as a strategic pillar for delivering the essential packages of health services. Methods: An explorative study following a qualitative approach has been conducted through semi-structured interviews to a convenience sample of 15 persons, selected as authoritative key-informants. Results: In addition to the lack of infrastructures, medicines, ambulances and health instruments, and the health disparities between the urban and rural areas, some widespread problems are reported as requiring health professionals’ training empowerment: traumas due to road accidents, management of childbirth, non-communicable diseases’ management and poor health education of the population. Discussion: Some areas can be evidenced for an improvement of professionals, training: ​​maternal, neonatal and child health; communication between professionals and laypeople; Myanmar population’s health education; inter-professional training between doctors and nurses, but also between health personnel and non-health personnel. Conclusions: The educational needs of Myanmar health professionals emerge as closely related to the social and health needs of the Myanmar population, to the available resources and missing resources of the country’s health system and to the role of professionals within professionals/patients’ relationship. (www.actabiomedica.it)